Comparative analysis of microscopic and molecular methods for the diagnosis and post-treatment monitoring of Echinococcus granulosus sensu stricto in experimentally infected dogs: Initial findings from digital PCR - Selcuk, Muhammed Ahmed; Celik, Figen; Simsek, Sami (Elsevier, 2025)
Cystic echinococcosis (CE), caused by Echinococcus granulosus sensu lato, is a significant zoonotic disease with profound public health and economic impacts. This study evaluated egg detection methods, molecular diagnostics, and post-treatment shedding dynamics in experimentally infected dogs. Three three-month-old male dogs were included in the study. Two experimental dogs (ED-1, ED-2) were orally infected with 20,000 E. granulosus protoscoleces, while one served as a control (CD). Stool samples were collected daily over 50 days post-infection and 30 days post-treatment. Detection of E. granulosus eggs was performed using the f & uuml;lleborn and sieving flotation methods. Genomic DNA was extracted, and molecular analysis was conducted via conventional PCR, Real-time quantitative PCR (qPCR), and digital PCR (dPCR). Egg detection in stool samples began on days 44-46 post-infection using flotation methods, while PCR detected parasite DNA as early as day 20. Both qPCR and dPCR consistently detected parasite DNA from day 1 to day 50 post-infection, with increased sensitivity observed after day 23. Treatment eliminated viable egg shedding within 2-4 days and post-treatment monitoring revealed intermittent detection up to day 30, with dPCR identifying copy numbers even when qPCR Ct values were undetectable. These findings highlight the superior sensitivity of molecular methods in early detection and their persistence in identifying DNA beyond egg-shedding periods. This raises important questions about interpreting molecular positivity in the prepatent phase and its implications for surveillance and diagnostics.
Keywords: Echinococcus granulosus; Dog; Egg; Microscopy; PCR; QPCR; Digital PCR